How consumers' economic and psychological vulnerabilities impact their consumption regulation during crisis - Karaosmanoglu, Elif; Okan, Mehmet; Işıksal, Didem Gamze; Altinigne, Nesenur; Demir, Ozge; İdemen, Elif (Wiley, 2024)
AbstractThis paper focuses on the economic and psychological vulnerabilities that are intensified due to the effects of the COVID‐19 pandemic on individuals' health, education and living standards. The deteriorating mental and financial conditions of individuals, called psychological and economic vulnerability, have made an impact on consumers' consumption patterns and habits. This study has proposed that when consumer vulnerabilities increase, consumers will be more likely to express prosocial behaviours and assume higher social capital change that may influence their consumption regulations. The findings are based on a panel survey of 786 individuals via CATI in two waves of data collection in Türkiye (Wave I: 20 July–10 August 2020; Wave II: 20 November–10 December 2020). In Wave I, it is found that when individuals face economic and psychological vulnerability, their tendency to show prosocial behaviour is negatively affected. In Wave II, when the COVID‐19 cases peaked, while economic vulnerability still leads to lower prosocial behaviour, psychological vulnerability gets reversed and results in higher prosocial behaviour. Interestingly, in both waves, when consumers perceive positive social capital change due to increased prosocial behaviour, they are less likely to show consumption regulation.